Exemplification and stigmatization: How news stories affect stigma-related attitudes, emotional reactions, and behavioral intentions towards students with a disability - Hastall, Matthias R.; Röhm, Alexander; Kotarski, Claudia; Meißner, Sina; Ritterfeld, Ute (Frontiers in Communication, 2024)
Students with intellectual or physical disabilities still face public and institutional stigmatization. The current study examines how different news portrayals of college students with a disability affect readers' stigma-related attitudes and behavioral intentions. A 2 × 2 × 2 × 2 full-factorial experiment was conducted, in which N = 767 respondents were presented a news article about a student with a disability. The article was manipulated regarding exemplar's type of disability, gender, socioeconomic status, and sexual orientation. All four tested exemplar characteristics and respondents' gender affected several dimensions of stigmatization, albeit often as interaction effects. Overall, findings indicate that story-unrelated characteristics of portrayed individuals affect readers' generalized stigma-relevant attitudes, emotional reactions, and behavioral intentions. Results are discussed regarding the likelihood for accidental stigmatization through journalistic exemplar choices, and regarding implications for a stigma-sensitive health communication and anti-stigma communication practice.